Organizational Training and Organizational Commitment: A Literature Review and Conceptual Development - Dias, Á.; Silva, Rui (International Journal of Innovative Science, Engineering and Technology, 2016)
In a global economy without barriers that provide protection to the organizations, all available resources are critical to achieving success and market leadership. People, i.e. employees, assume a leading role in the weapons that the organizations have. Organizations seek, globally, the best employees. Attract and retain the best employees motivated is vital for any organization that wants to distinguish. Organizational training is privileged to attract knowledge to the organization, which in, addition to traditional benefits, can contribute and play a leading role in motivating and retaining the best employees. The purpose of this article is to make a literature review of organizational training, and organizational commitment, as well as the already studied relationship between the constructs.